5-FU-Induced Upregulation of Exosomal PD-L1 Causes Immunosuppression in Advanced Gastric Cancer Patients - Zhang, Min; Fan, Yibo; Che, Xiaofang; Hou, Kezuo; Zhang, Chaoxu; Li, Ce; Wen, Ti; Wang, Shuo; Cheng, Yu; Liu, Yunpeng; Qu, Xiujuan (Frontiers in Oncology, 2020)
Although the cytotoxic chemotherapeutic agent 5-fluorouracil (5-FU) is generally considered to directly kill cancer cells and exert immunostimulatory effects in advanced gastric cancer, accumulating evidence indicates that it upregulates the expression of PD-L1, a representative immune checkpoint blockade molecule involved in negative regulation of the immune response. It was reported that exosomes could transfer functional PD-L1 locally and distantly to suppress the antitumor immune response. However, whether 5-FU alters the expression of exosomal PD-L1 and induces immunosuppression in gastric cancer remains unclear. Herein, we found that 5-FU increased gastric cancer-derived exosomal PD-L1. Importantly, compared with baseline levels, circulating exosomal PD-L1 was significantly upregulated in 21 stage Ⅲ-Ⅳ gastric cancer patients after 2, 4 and 6 repeated cycles of fluoropyrimidine treatment (P=0.009, P=0.047 and P=0.023, respectively), accompanied by decreased amounts of IFN-γ, TNF-α, IL-2, IL-6 and GM-CSF (P=0.014, P=0.004, P=0.009, P=0.031 and P=0.014, respectively). Additionally, circulating exosomal PD-L1 was increased more significantly in clinical non-responders compared with responders (P=0.018). Furthermore, exosomal PD-L1 induced apoptosis in Jurkat T cells and inhibited T cells activation in PBMCs, which could be partly reversed by nivolumab. These results suggested that 5-FU-induced upregulation of exosomal PD-L1 causes systemic immunosuppression in advanced gastric cancer following multiple cycles of chemotherapy, especially after 2 cycles.